INOVASI KEPEMIMPINAN KEPALA SEKOLAH SEBAGAI PENGGERAK MANAJEMEN BERBASIS SEKOLAH (MBS) DI SD NEGERI 1 PEDUNGAN - Anak Agung Gede Agung; Chindytia; I Putu Yoga Agasthia Dharma Putra; I Made Adi Wira Nata; I Komang Ari Utama Krisnajaya (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to describe the principal’s leadership innovation as a driving force of School-Based Management (SBM) at SD Negeri 1 Pedungan. This research employed a descriptive qualitative approach using interviews, observation, and documentation as data collection techniques. The findings reveal that the principal implemented various leadership innovations, including digital-based learning development, character education strengthening, school environment development, and transparent communication with school stakeholders and the community. These innovations have positively contributed to improving the quality of learning, student achievement, teacher professionalism, and the participation of parents and society. Therefore, principal leadership innovation plays a crucial role in optimizing the implementation of SBM and enhancing the quality of education in elementary schools.